Chronic Obstructive Pulmonary Disease (COPD): Diagnosis, Pathology, Clinical Presentation and Homoeopathic Management - Pathak, Praveen Kumar; Pathak, Shiwani (Journal for Research in Applied Sciences and Biotechnology, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a very common problem worldwide now a day. COPD is preventable and treatable disease it is characterized by constant airflow limitation that is generally progressive and connected with an enhanced chronic inflammatory response in the airways and the lung to noxious particles or gases. Exacerbations and comorbidities contribute to the generally severity in individual patients of COPD. It remains a most important reason of morbidity and mortality globally and outcome in an economic and social burden that is both substantial and increasing.